Application of Room‐Temperature Aprotic and Protic Ionic Liquids for Oxidative Folding of Cysteine‐Rich Peptides. Issue 18 (5th November 2014) - Heimer, Pascal; Tietze, Alesia A.; Böhm, Miriam; Giernoth, Ralf; Kuchenbuch, Andrea; Stark, Annegret; Leipold, Enrico; Heinemann, Stefan H.; Kandt, Christian; Imhof, Diana
Abstract The oxidation of the conotoxin μ‐SIIIA in different ionic liquids was investigated, and the results were compared with those obtained in [C2mim][OAc]. Conversion of the reduced precursor into the oxidized product was observed in the protic ILs methyl‐ and ethylammonium formate (MAF and EAf, respectively), whereas choline dihydrogenphosphate and Ammoeng 110 failed to yield folded peptide. However, the quality and yield of the peptide obtained in MAF and EAF were lower than in the case of the product from [C2mim][OAc]. Reaction conditions (temperature, water content) also had an impact on peptide conversion. A closer look at the activities of μ‐SIIIA versions derived from an up‐scaled synthesis in [C2mim][OAc] revealed a significant loss of the effect on ion channel NaV1.4 relative to the buffer‐oxidized peptide, whereas digestion of either μ‐SIIIA product by trypsin was unaffected. This was attributed to adherence of ions from the IL to the peptide, because the disulfide connectivity is basically the same for the differentially oxidized μ‐SIIIA versions.